Clinical features of acquired erythrocytosis: Low levels of serum erythropoietin in a subset of non‐neoplastic erythrocytosis patients. (1st July 2022) - Mori, Yosuke; Araki, Marito; Morishita, Soji; Imai, Misa; Edahiro, Yoko; Ito, Masafumi; Ochiai, Tomonori; Shirane, Shuichi; Hashimoto, Yoshinori; Yasuda, Hajime; Ando, Jun; Ando, Miki; et al.
Abstract: Background: Acquired erythrocytosis can be classified into polycythemia vera (PV) and non‐neoplastic erythrocytosis (NNE). The vast majority of PV patients harbor JAK2 mutations, but differentiating JAK2 mutation‐negative PV from NNE is challenging due to a lack of definitive molecular markers. Methods: We studied the clinical features of 121 patients with erythrocytosis of which 47 (38.8%) were JAK2 mutation‐positive and also fulfilled the diagnostic criteria for PV, and 67 (55.4%) JAK2 mutation‐negative erythrocytosis patients who were diagnosed as NNE. Diagnosis was strictly based on driver mutation analysis and central pathology review. Results: No JAK2 mutation‐negative PV patients were found in our cohort. The NNE group showed significantly younger ( p < 0.01) age with higher frequency of smoking ( p < 0.001), alcohol consumption ( p < 0.001), and diabetes mellitus ( p < 0.05), whereas the PV group ( n = 47) showed significantly higher white blood cell count, platelet count, and lactate dehydrogenase ( p < 0.001). Although serum erythropoietin (EPO) levels were significantly higher in NNE compared to PV ( p < 0.001), approximately 40% of the NNE patients had EPO levels below the lower range of normal, fulfilling a minor diagnostic criterion of PV and raising the possibility of PV misdiagnosis. Conclusion: Low EPO levels in JAK2 mutation‐negative erythrocytosis may not be a reliable diagnostic criterion for distinguishing PV from NNE. Abstract : Heat maps illustrating lifestyle habits and pre‐existing clinical conditions at the time of initial diagnosis in non‐neoplastic erythrocytosis (NNE) and polycythemia vera patients. Black, white, and gray indicate presence, absence, and unknown status, respectively. The NNE group showed a higher frequency of smoking, alcohol consumption, and type 2 diabetes mellitus.